Art and politics in the support of scopic regimes (ALPHA. Journal of Arts, Literature and Philosophy, 2022)
This article studies the power of visual aesthetics in politics. Between what is allowed to see and what is forbidden to show, the scopic regime is defined by the intervention of institutional power on the viewer's gaze. This study is developed between the philosophical tradition and other multidisciplinary contributions (visual studies, social communication, aesthetics, art history, art theory) that show a) political control in the scopic regimes of the viewer's gaze; b) the consolidation of a visual culture that conditions the way of life of individuals and societies; c) the domain of social space through the regulation of visual space; and d) the manipulation of affects through visual experience. In this study we highlight the opening of critical consciousness in modernity to the aestheticization of politics.
Keywords: Scopic Regime; aesthetics; visuality; politics; art